COMPETÊNCIAS E FUNÇÃO GERENCIAL: DESVENDANDO O GAP (LACUNA) DE COMPETÊNCIAS DE GESTORES PÚBLICOS DO NÚCLEO DE EDUCAÇÃO DE UMA UNIVERSIDADE FEDERAL BRASILEIRA - Patricia Whebber Souza Oliveira (Universidade Federal de Santa Catarina, 2013)
This study aimed to analyze the gap and managerial competencies required and actual, basing on the roles and responsibilities of the managerial function in the perception of managers and servers at the Center for Childhood Education (NEI) from a Brazilian Federal University. The study is characterized as a qualitative research, and the participants were managers and servers. The data collection techniques were interviews and questionnaires. For the data processing, was used the content analysis. The results indicate the existence of required competencies for the exercise of the management, and these are considered to be present in the actions of managers and there is no gap of current competencies. Among the competencies identified, stood out: domain expertise to education, interpersonal relationships, tolerance, future vision, commitment and responsibility, democratic posture, flexibility and adaptation to change. We conclude that the perception of the participants, there is no gap in competencies, ho wever, there is need for improvement in competencies: interpersonal relationships and communication, considered of fundamental importance in the context of educational administration.